Sita's Ramayana - Arni, Samhita (Groundwood Books/House of Anansi Press, 2011)
This version of The Ramayana is told from the perspective of Sita, the queen. It is an allegorical story that contains important Hindu teachings, and it has had great influence on Indian life and culture over the centuries.